Biochar as a fuel: 3. Mechanistic understanding on biochar thermal annealing at mild temperatures and its effect on biochar reactivity - Yip, Kong; Xu, M.; Li, Chun-Zhu; Jiang, San Ping; Wu, Hongwei (American Chemical Society, 2011)
This study reports a mechanistic investigation on the thermal annealing process at mild temperatures (750 and 900 C) and its effect on the reactivity of biochar prepared from the pyrolysis of a Western Australia mallee wood. A range of analyses were carried out, including biochar oxidation reactivity, inorganic species, oxygen and hydrogen contents in the biochars, release of heteroatoms in biochar as the gaseous product, and biochar structural evolution during thermal annealing. Extensive thermal annealing (up to 600 min) of biochars at 750 and 900 C leads to little loss of inorganic species from the biochars. Fourier transform (FT)-Raman spectroscopic analysis further shows that thermal annealing induces a progressively more ordered carbonaceous structure with an increase in the temperature and thermal annealing time. The process is coupled with the loss of heteroatoms, released as dominantly H2 and to a less extent CO. The effect of thermal annealing is drastic during the initial period up to 60 min and levels off with further holding at the annealing temperatures. As thermal annealing progresses, a carbon structural transformation clearly takes place and condenses at least part of the reactive and amorphous structures into larger and more inert ring systems, although little graphitization of biochar carbon structure is evidenced. As a result, thermal annealing leads to a significant change in the biochar reactivity. In the absence of catalytic species, the reduction in biochar reactivity is due to the ordering of the carbon structure induced by thermal annealing. In the presence of catalytic species, the changes in biochar reactivity are results of changes in both the carbon structure and catalytic activity. The changes in the catalytic activity appear to suggest a change in the form and dispersion of the catalytic species within the biochars, as results of the loss of heteroatoms and carbon structure condensation.